Test–retest reliability of kinematic and kinetic parameters during dual-task stair walking in the elderly - Li, Yue; Yu, Ning; Zhang, Cui; Song, Qipeng; Wang, Jiangna; Sun, Wei (Frontiers in Physiology, 2023)
Objective: This study aims to evaluate the test–retest reliability of kinematics and kinetics during single and dual-task stair walking in the elderly. Methods: Sixteen healthy elderly adults (7 women, 8 men, 66.8±3.6 years old, 161.0±4.3 cm, 61.6±4.2 kg) were recruited. Kinematic and kinetic parameters were measured using an infrared motion analysis system (Vicon, Oxford Metrics Ltd., Oxford, UK) and force platforms (Switzerland, Kistler 9287BA and 9281CA). Participants were tested under single-task and dual-task (serial 3 subtractions or carrying a cup of water) conditions. Each participant completed two sessions on two separate days with a 1-week interval. Intraclass correlation coefficients (ICC), Pearson correlation coefficient (r), and Bland–Altman plot were used to assess the reliability of stair walking. Results: During ascending stair, the ICC of kinematics and kinetics ranged from fair to excellent (ICC=0.500-0.979) in the single and dual tasks, except for step length (ICC=0.394) in the single task. The r value of kinematics and kinetics ranged from 0.704 to 0.999. During stair descending, the ICC of kinematics and kinetics ranged from good to excellent (ICC=0.661-0.963), except for min hip moment (ICC=0.133) and min ankle moment (ICC=0.057) in the manual task. The r value of kinematics and kinetics ranged from 0.773 to 0.960 in the single and dual tasks. In the Bland–Altman plots, all the zero values and most of the dots fell in the 95% confidence interval, and the mean difference was found to be close to zero for all the parameters during stair walking. Conclusion: This study verified the fair to excellent reliability for kinematic and kinetic parameters under single condition and the fair to excellent reliability for kinematic parameters in the dual task during stair walking in the elderly. However, stride length, hip joint moment, and ankle joint moment should be cautiously recommended for assessing stair walking in the elderly population.